2022
DOI: 10.1038/s41598-022-19073-z
|View full text |Cite
|
Sign up to set email alerts
|

Activation of SARS-CoV-2 neutralizing antibody is slower than elevation of spike-specific IgG, IgM, and nucleocapsid-specific IgG antibodies

Abstract: COVID-19 antibody testing has been developed to investigate humoral immune response in SARS-CoV-2 infection. To assess the serological dynamics and neutralizing potency following SARS-CoV-2 infection, we investigated the neutralizing (NT) antibody, anti-spike, and anti-nucleocapsid antibodies responses using a total of 168 samples obtained from 68 SARS-CoV-2 infected patients. Antibodies were measured using an authentic virus neutralization assay, the high-throughput laboratory measurements of the Abbott Alini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Infection status was assessed serologically at the beginning and at the end of the observation period, determining the IgG seropositivity to the SARS-CoV-2 anti-N protein, and on the basis of the reported positive swabs. Indeed, it is known that anti-N IgG positivity correlates with natural exposure to SARS-CoV-2; hence, it is considered a good indicator of previous infections [ 30 , 31 ]. Recent findings have demonstrated that the seroreversion of anti-N antibodies occurs at a minimum of 7–8 months after seroconversion, which typically takes place 14–21 days after SARS-CoV-2 infection [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infection status was assessed serologically at the beginning and at the end of the observation period, determining the IgG seropositivity to the SARS-CoV-2 anti-N protein, and on the basis of the reported positive swabs. Indeed, it is known that anti-N IgG positivity correlates with natural exposure to SARS-CoV-2; hence, it is considered a good indicator of previous infections [ 30 , 31 ]. Recent findings have demonstrated that the seroreversion of anti-N antibodies occurs at a minimum of 7–8 months after seroconversion, which typically takes place 14–21 days after SARS-CoV-2 infection [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the neutralizing activity of samples from the four different panels was tested with the cell culture-based VNT and two sVNTs, cPass and NeutraLISA. As NAbs are usually detected later than non-neutralizing IgG [ 38 , 39 , 40 ], the early detection of NAbs in T1 (0–5 dpso/dpPCR) by all three NTs was surprising. As dpso and dpPCR were equalized in this study and samples from panel A were analyzed irrespective of disease severity, the detectability of NAbs might shift to earlier times.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, S-IgG and NT-IgG were strongly correlated in Japanese post-renal transplant patients. It has been reported that when the neutralizing activity of S-IgG was measured in the general population infected with COVID-19, a certain number of NT-IgG-negative individuals were also found among the S-IgG-positive individuals [ 19 ]. Most of the S-IgG-positive renal transplant recipients in this study were NT-IgG-positive, except only two with low S-IgG antibody titers were NT-IgG-negative.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, S-IgG titers were measured 5–6 months after the second vaccination and 3 weeks to 3 months after the third vaccination in post-kidney-transplant patients in Japan, and changes in the persistence of antibody titers and antibody-acquisition rate following the third vaccination were examined. Because S-IgG alone cannot dictate the ability to protect against infection, S-IgG and neutralizing antibodies (NT-IgG) do not necessarily correlate in the general population [ 19 ]; NT-IgG was also measured.…”
Section: Introductionmentioning
confidence: 99%